Health communication theoretical and critical perspectives - Cross, Ruth; Davis, Sam 1968-; O'Neil, Ivy; Davis, Sams (Polity Press, 2017)
Health communication is key to promoting good population and individual health outcomes. As the field has developed, there is a growing need for a critical appraisal of the ideologies and theories underpinning health communication in order to ensure effective practice. This text outlines key issues in the field.